Fertility Transitions Along the Extensive and Intensive Margins - Aaronson, Daniel; Lange, Fabian; Mazumder, Bhashkar (American Economic Review, 2014)
By allowing for an extensive margin in the standard quantity-quality model, we generate new insights into fertility transitions. We test the model on Southern black women affected by a large-scale school construction program. Consistent with our model, women facing improved schooling opportunities for their children were more likely to have at least one child but chose to have smaller families overall. By contrast, women who themselves obtained more schooling due to the program delayed childbearing along both the extensive and intensive margins and entered higher quality occupations, consistent with education raising opportunity costs of child rearing. (JEL I20, J13, J15, J16, J24)